Carotid body autotransplantation in Parkinson disease: a clinical and positron emission tomography study. Issue 8 (12th January 2007) - Mínguez-Castellanos, Adolfo; Escamilla-Sevilla, Francisco; Hotton, Gary R; Toledo-Aral, Juan J; Ortega-Moreno, Ángel; Méndez-Ferrer, Simón; Martín-Linares, José M; Katati, Majed J; Mir, Pablo; Villadiego, Javier; Meersmans, Miguel; Pérez-García, Miguel; et al.
Abstract : Background: Carotid body (CB) glomus cells are highly dopaminergic and express the glial cell line derived neurotrophic factor. The intrastriatal grafting of CB cell aggregates exerts neurotrophic actions on nigrostriatal neurons in animal models of Parkinson disease (PD). Objective: We conducted a phase I–II clinical study to assess the feasibility, long term safety, clinical and neurochemical effects of intrastriatal CB autotransplantation in patients with PD. Methods: Thirteen patients with advanced PD underwent bilateral stereotactic implantation of CB cell aggregates into the striatum. They were assessed before surgery and up to 1–3 years after surgery according to CAPIT (Core Assessment Programme for Intracerebral Transplantation) and CAPSIT-PD (Core Assessment Programme for Surgical Interventional Therapies in Parkinson's Disease) protocols. The primary outcome measure was the change in video blinded Unified Parkinson's Disease Rating Scale III score in the off-medication state. Seven patients had 18 F-dopa positron emission tomography scans before and 1 year after transplantation. Results: Clinical amelioration in the primary outcome measure was observed in 10 of 12 blindly analysed patients, which was maximal at 6–12 months after transplantation (5–74%). Overall, mean improvement at 6 months was 23%. In the long term (3 years), 3 of 6 patients still maintained improvement (15–48%). None of the patients developed off-period dyskinesias. The main predictive factors for motor improvement were the histological integrity of the CB and a milder disease severity. We observed a non-significant 5% increase in mean putaminal 18 F-dopa uptake but there was an inverse relationship between clinical amelioration and annual decline in putaminal 18 F-dopa uptake (r = −0.829; p = 0.042). Conclusions: CB autotransplantation may induce clinical effects in patients with advanced PD which seem partly related to the biological properties of the implanted glomus cells.